Proteins of TNF-α and IL6 Pathways Are Elevated in Serum of Type-1 Diabetes Patients with Microalbuminuria - Purohit, Sharad; Sharma, Ashok; Zhi, Wenbo; Bai, Shan; Hopkins, Diane; Steed, Leigh; Bode, Bruce; Anderson, Stephen W.; Reed, John Chip; Steed, R. Dennis; She, Jin-Xiong (Frontiers in Immunology, 2018)
Soluble cytokine receptors may play an important role in development of microalbuminuria (MA) in type-1 diabetes (T1D). In this study we measured twelve soluble receptors and ligands from TNF-α/IL-6/IL-2 pathways in T1D patients with MA (n=89) and T1D patients without MA (n=483) participating in the PAGODA study. Twelve proteins in the sera from T1D patients with and without MA were measured using multiplex Luminex assays. Ten serum proteins (sTNFR1, sTNFR2, sIL2Rα, MMP2, sgp130, sVCAM1, sIL6R, SAA, CRP and sICAM1) were significantly elevated in T1D patients with MA. After adjusting for age, duration of diabetes and sex in logistic regression, association remained significant for seven proteins. MA is associated with increasing concentrations of all ten proteins, with the strongest associations observed for sTNFR1 (OR=108.3, P<10-32) and sTNFR2 (OR=65.5, P<10-37), followed by sIL2Rα (OR=12.9, P<10-13), MMP2 (OR=5.5, P<10-6), sgp130 (OR=5.2，P<10-3), sIL6R (OR=4.6, P<10-4) and sVCAM1 (OR=3.3, P<10-4). We developed a risk score system based on the combined odds ratios associated with each quintile for each protein. The risk scores cluster MA patients into three subsets, each associated with distinct risk for MA attributable to proteins in the TNF-α/IL6 pathway (mean OR=1, 13.5, and 126.3 for the three subsets, respectively). Our results suggest that the TNF-α/IL6 pathway is overactive in approximately forty percent of the MA patients and moderately elevated in the middle forty percent of the MA patients. Our results suggest the existence of distinct subsets of MA patients identifiable by their serum protein profiles.